Autophagy and Exosome Coordinately Enhance Macrophage M1 Polarization and Recruitment in Influenza A Virus Infection - Xia, Chengjie; Xu, Weiming; Ai, Xin; Zhu, Yingqi; Geng, Ping; Niu, Yijun; Zhu, Haiyan; Zhou, Wei; Huang, Hai; Shi, Xunlong (Frontiers in Immunology, 2022)
Background Influenza A virus infection results in viral pneumonia, which is often accompanied by the infiltration and recruitment of macrophages, overactivation of inflammatory responses, and obvious cell autophagy and exosome production. However, little is known about the roles of autophagy and exosome production in these inflammatory responses. Methods In this study, multiple methods, such as flow cytometry, real-time quantitative reverse transcription-polymerase chain reaction, immune–fluorescence technology, and western blot, were applied to explore the possible effects of autophagy and exosome production by H1N1-infected host cells. Results It was observed that a high number of polarized macrophages (CD11b+/F4/80+/CD86+) were recruited to the lung tissues of infected mice, which could be mimicked by tracking the movement of macrophages to H1N1-infected cells in vitro (transwell assays). Furthermore, there was some coordinated upregulation of M1 polarization signs (iNOS/Arg-1 bias) as well as autophagy (LC3) and exosome (CD63) biomarkers in the infected macrophages and epithelial cells. Moreover, exosomes extracted from the supernatant of virus-infected cells were shown to promote the recruitment and polarization of more peritoneal macrophages than the normal group. The fluorescence colocalization of LC3-CD63 and the inhibition of autophagy and exosome signaling pathway further revealed that H1N1 infection seemed to sequentially activate the M1 polarization and recruitment of macrophages via autophagy–exosome dependent pathway. Conclusion Autophagy and exosome production coordinately enhance the M1 polarization and recruitment of macrophages in influenza virus infection, which also provides potential therapeutic targets.